2014
DOI: 10.5114/aoms.2013.36927
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of phospho-PRAS40 (Thr246) expression in gastric cancer

Abstract: IntroductionsPhospho-PRAS40Thr246 (phosphorylated proline-rich Akt substrate of 40 kilodaltons at Thr246) is a biomarker for phosphatidylinositol 3-kinase (PI3K) pathway activation and AKT inhibitors sensitivity.Material and methodsIn this study, we immunohistochemically investigated the expression of phospho-PRAS40Thr246 in 141 gastric cancer tumors, and evaluated its clinicopathological and prognostic significance.ResultsSixty-four cases (45.4%) were defined as phospho-PRAS40Thr246 positive. Phospho-PRAS40Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…It has been reported that diabetic treatments correlate with increased cancer risk, but the literature linking the two pathologies is equivocal. Even though PRAS40 has been identified as a predictive protein biomarker for diverse cancers [22,23], its use as a dual prognostic marker in the pathophysiological prognosis of both cancer and diabetes remains to be elucidated. Such a dual biomarker would be quite valuable, as patients suffering from diabetes also have a higher risk of cancer [24,25].…”
Section: Role Of Pras40 In Diabetes and Other Metabolic Disordersmentioning
confidence: 99%
“…It has been reported that diabetic treatments correlate with increased cancer risk, but the literature linking the two pathologies is equivocal. Even though PRAS40 has been identified as a predictive protein biomarker for diverse cancers [22,23], its use as a dual prognostic marker in the pathophysiological prognosis of both cancer and diabetes remains to be elucidated. Such a dual biomarker would be quite valuable, as patients suffering from diabetes also have a higher risk of cancer [24,25].…”
Section: Role Of Pras40 In Diabetes and Other Metabolic Disordersmentioning
confidence: 99%
“…Another protein with markedly reduced phosphorylation in MKN45 is the proline-rich AKT substrate of 40-kDa (PRAS40) which inhibits the activity of the mTOR complex 1 (mTORC1) kinase. Phosphorylation of PRAS40 by Akt and by mTORC1 itself results in activation of mTORC1 activity and enhancement of cell survival and growth via activation of p-70S6K and 4-EBP1 [43][44][45]. Accordingly, phosphorylation of 70S6K und Akt is downregulated in MKN45 cells in response to ganetespib.…”
Section: Mkn1mentioning
confidence: 88%
“…The semi-quantitation revealed that CREB, PRAS40, HSP60 and WNK1 were decreased prominently in SYO-1 (Table 1). Because CREB, PRAS40, HSP60 and WNK1 were considered to contribute to aggressive phenotypes such as tumour progression and metastases20212223, we speculated that their downregulation would be less likely to cause the aggressive phenotype of resistant clones. Further investigations are warranted to determine their roles in pazopanib resistance.…”
Section: Discussionmentioning
confidence: 99%